Revisiting Justice in Inclusive Education: A Case Study of Jombang - Ahmad Sholikhin Ruslie; Tina Fitria Ningtyas; Nata Senora; M. Ja'far Raihan Alfath; Maulana Berlian (Mimbar Keadilan, 2025)
Inclusive education has become a fundamental principle within the Indonesian education system as an effort to ensure equal rights for all children, including those with special needs. However, the implementation of inclusive education policies at the regional level, particularly in Jombang Regency, reveals a gap between normative discourse and the reality of practice on the ground. The Jombang Regent Regulation No. 39 of 2014 serves as the legal basis for the implementation of inclusive education; however, its application does not fully reflect the principle of substantive justice for children with special needs. This study aims to critique the policy using philosophical and normative approaches to analyze the role of the state as the organizer of inclusive education. The methodology employed is a qualitative approach with textual analysis of legislation and observation of policy implementation in inclusive schools in Jombang. The research findings indicate that although inclusive education policies are legally and formally regulated, many deficiencies persist in practice, such as the lack of support teachers, unprepared curricula, and insufficient funding. These findings reflect the state's failure to uphold the principles of social justice and human rights for children with special needs. Inclusive education should be understood as an integral part of the state's obligation to achieve substantive justice, rather than merely an administrative requirement.